Antioxidant response of tobacco (Nicotiana tabacum) hairy roots after phenol treatment - Sosa Alderete, Lucas Gastón (2011)
Phenol is released to the environment from a wide variety of industrial effluents and it causes severe problems to human health and ecosystem. In the present study, we determined that Nicotiana tabacum hairy roots (HRs) double transgenic (DT) for two peroxidase genes (tpx1 and tpx2) showed higher phenol removal efficiency than wild type (WT) HRs after 120 h of phenol treatment at the expense of endogenous H 2O 2. Besides, to determine whether phenol could induce oxidative stress on tobacco HRs, we analyzed the antioxidant response, superoxide anion (O 2 -) localization and malondialdehyde (MDA) levels. Both HRs treated with phenol, showed significant increases in peroxidase (PX) activity mainly at the end of the assay (120 h) being PX activity from transgenic HRs 40% higher than that of WT HRs. Superoxide dismutase (SOD) and ascorbate peroxidase (APX) activities showed significant increases from 24 to 120 h of phenol treatment. PX, SOD and APX isoforms were also analyzed and slight changes were observed only in PX patterns. Both HRs showed significant differences in total glutathione (TGSH) content during treatment, being higher in DT HRs than in WT HRs. At the end of the assay, a greater accumulation of O 2 - in different root zones was observed in WT and DT HRs. Moreover, phenol was able to increase the MDA levels in WT HRs from 48 to 120 h of the treatment, but no significant changes were observed in DT HRs. Results suggest that under these experimental conditions, DT HRs would be more tolerant to phenol than WT HRs.